The Effect of Asthma Gymnastics on Peak Expiratory Flow among Asthma Patients - Kusuma, Erik; Handayani, Dwining; Puspitasari, R.A. Helda; Nastiti, Ayu Dewi (Global Health Science Group, 2024)
Asthma is a chronic inflammation that results in bronchospasm and bronchoconstriction that cause weakness of the respiratory muscles, resulting in a decrease in respiratory ability. One of the efforts to correct these disturbances is made by doing asthma gymnastics. Objective: This study aims to identify the influence of asthma gymnastics on the peak expiratory flow among asthma sufferers. Method: This type of research was a pre-experiment with a pretest-posttest design. The sample in this study is composed of 31 asthma patients selected using the total sampling technique. Data analysis using paired t-test with α significant level of 0.05. Results: As a result of the asthma exercise, the Peak Respiratory Flow (PEF) increased to 304 lt/min from 208 lt/min before the exercise (p 0.000 < 0.05). There was an effect of asthma gymnastics on peak respiratory flow among asthma patients at the Asthma Polyclinic of Bangil Hospital. Conclusions: Regular asthma gymnastics can improve breathing ability, as indicated by peak respiratory flow, and improve the quality of life of asthma sufferers.